Prevalencia de parásitos intestinales en escolares de Ciudad Bolívar, Venezuela: comparación entre dos períodos - Devera Rodolfo; Blanco Ytalia; Amaya Iván (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2015)
Abstract; The prevalence of intestinal parasites in 921 schoolchildren from nine schools in Ciudad Bolivar, Bolivar State, Venezuela during the period 2009-2013 was determined and compared with that obtained in the same city in the period 1995-1996 in seven schools and 446 children. At the first opportunity the fecal samples were analyzed by direct examination and Willis technical; while for the second, feces were submitted to direct, Kato and spontaneous sedimentation. The overall prevalence of intestinal parasites for the periods 1995-1996 and 2009-2013 was 52% and 62.9% respectively. In the first period, the helminths prevailed and the second, the Chromistas-Protozoa group turned more prevalent. For 1995-1996, the helminths Trichuris trichiura (24.2%) and Ascaris lumbricoides (19.5%) were more common; while for the period 2009-2013, the Chromista Blastocystis spp. was the most prevalent (47.6%), followed by protozoan Endolimax nana (17.7%). In all these cases the difference was significant (p <0.05) when the prevalence of both periods being compared. We conclude that there was a change in the prevalence of intestinal parasites in the study population: in the first period (1995-1996) dominated the helminths and the second (2009-2013) the Chromista Blastocystis spp. and protozoa. Resumen; Se determinó la prevalencia de parásitos intestinales en 921 escolares de 9 escuelas de Ciudad Bolívar, estado Bolívar, Venezuela durante el período 2009-2013 y se comparó con la obtenida en la misma ciudad en el período 1995-1996, en 7 escuelas y 446 niños. En la primera oportunidad las muestras fecales fueron analizadas mediante examen directo y técnica de Willis; mientras que, para la segunda, las heces fueron sometidas al directo, Kato y sedimentación espontánea. La prevalencia general de enteroparásitos para los períodos 1995-1996 y 2009-2013 fue de 52% y 62,9% respectivamente. En el primer período prevalecieron los helmintos y para el segundo el grupo de Chromistas-Protozoarios resulto más prevalente. Para 1995-1996, los helmintos Trichuris trichiura (24,2%) y Ascaris lumbricoides (19,5%) resultaron más comunes; mientras que para el período 2009- 2013, el chromista Blastocystis fue el más prevalente (47,6%), seguido del protozoario Endolimax nana (17,7%). En todos esos casos la diferencia fue significativa (p<0,05) cuando se comparan las prevalencias de ambos períodos. Se concluye que hubo un cambio en la prevalencia de los parásitos intestinales en la población evaluada: en el primer período (1995-1996) predominaron los helmintos y para el segundo (2009-2013) el chromista Blastocystis spp. y los protozoarios.